Giving body to the ideas: Performance as a process of embodiment (Orfeu, 2021)
This essay aims to discuss performance, not only as transitory and spontaneous dimension, but also wondering about the materials to be performed, as textual dimension (technical, aesthetical, and values), which, as a spectrum, circulates over the imagination of a certain community and it manifests itself during the performance, incorporating itself in the social body. Through authors such as Shelamay and Appadurai, it is possible to understand the performative practice as representations and encenation of these texts, and at the same time, as a way to introject them in subjects, creating unity in those communities, enabling its reproduction.  So, it is possible to imagine the performance as a reincarnation of old values and meanings, which returns, as imaginary reminiscence, walking among the livings, modeling their histories.
Keywords: Musical communities; Locality; Ideology; Popular music; Musical performance